2018
DOI: 10.2166/wst.2018.255
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ecotoxicological effects of ciprofloxacin in Daphnia magna: life-history traits, biochemical and genotoxic effects

Abstract: Antibiotics (e.g. ciprofloxacin) have been detected in surface water and groundwater for several decades. In order to understand the potential impact of the continuous exposure of aquatic organisms to ciprofloxacin, a chronic assay was carried out with Daphnia magna. This approach allowed evaluation of the effects of ciprofloxacin on life-history and sub-individual parameters (antioxidant status and metabolic response: activities of catalase and glutathione S-transferases - GSTs; peroxidative damage; thiobarbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…This result suggested that more evident genotoxic damage could be revealed by longer haemocyte exposure time, as recently observed in clam haemocytes exposed in vitro the new PFAS C6O4 (Fabrello et al, 2021). A significant increase in genetic damage index was detected in Daphnia magna starting from 0.013 mg/L of ciprofloxacin (Nunes et al, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…This result suggested that more evident genotoxic damage could be revealed by longer haemocyte exposure time, as recently observed in clam haemocytes exposed in vitro the new PFAS C6O4 (Fabrello et al, 2021). A significant increase in genetic damage index was detected in Daphnia magna starting from 0.013 mg/L of ciprofloxacin (Nunes et al, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…In addition, Dionísio et al (2020) highlighted that low levels of ciprofloxacin (0.0125–0.0625 mg/L) produced damage to the neuronal membrane due to an increase in thiobarbituric acid reactive substances (TBARS) in a chronic study (21 days) of D. magna . Similarly, Nunes et al (2018) report an increase in TBARS levels in adults exposed to 0.078 mg/L of ciprofloxacin (concentration, which is within the range 0.056–3.600 mg/L, Table 2, of this work) causing a decrease in the antioxidant defense of D. magna .…”
Section: Discussionsupporting
confidence: 74%
“…The toxicity of FQs on D. magna is due to the inhibition of the eukaryotic topoisomerase II enzyme that participates in the cellular replication of this cladocero (Hooper & Jacoby, 2016). In this regard, Nunes et al (2018) demonstrated that concentrations of 0.013 mg/L of ciprofloxacin induce genotoxic effects on D. magna .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Daphnia is recognized as a sentinel species of freshwater ecosystems because its decline is an indicator of environmental impacts [3]. This characteristic associated with parthenogenic reproduction, short life cycle, high fecundity, and easy laboratory maintenance, makes them commonly used tool in toxicity assessments [11][12][13][14][15][16][17]. Normally, these organisms are maintained in laboratory conditions during several generations for use in biological research.…”
Section: Introductionmentioning
confidence: 99%